Profiling Rhodes University students' substance use during the Covid-19 pandemic lockdown: comparing the AUDIT and CCAPS-62 substance abuse sub-scale - Goosen, Jeslyn Chrismaré (Rhodes University, Faculty of Humanities, Department of Psychology)
Students are vulnerable to academic distress and mental health concerns. Many struggle to effectively cope with the many demands placed on them from various factions; included but not limited to institutional demands, financial concerns, and parental expectations. With the most recent outbreak of the SARS-Co V-2 (better known as the COVID-19 pandemic) many students have struggled to effectively cope with the changes relating to the nationwide lockdown. Universities had to change the way in which they provide students with the necessary academic material, and many had to return to their familial homes. This had a deleterious effect on the way students performed their daily activities and coping. A rise in impaired mental health was noted. Many students used alcohol as a means of coping during this tumultuous and unprecedented time. Undergraduate students at Rhodes University were asked to complete a survey questionnaire via SurveyMonkey, an online survey service. Data was collected over a ten-day period during July 2020. The AUDIT and the CCAPS-62 Substance Use subscale were used to measure their alcohol intake during lockdown and results was compared. Results indicated a significant positive correlation between the CCAPS-62 substance use subscale and the AUDIT (r = 0.80, n = 930, p < 0.01). Outcomes identified that men tend to drink more than females, and white students tend to drink more than black students. Findings suggests that the CCAPS-62 a multidimensional instrument measuring general distress among students could positively contribute to the reliability and validity of the measure used in a multicultural and multilingual society such as South Africa.
Keywords: College students Substance use -- South Africa -- Makhanda; College students Alcohol use -- South Africa -- Makhanda; College students Mental health -- South Africa -- Makhanda; College students Attitudes; College students Economic conditions; COVID-19 (Disease); Rhodes University